Implementasi Program â€œKeluar Bersamaâ€ dalam Inovasi Pelayanan Publik di Kecamatan Danurejan Kota Yogyakarta (Universitas Medan Area, 2019)
This research discuss about innovation â€œKeluar Bersamaâ€ in Danurejan Subdistrict Yogyakarta City. The research was carried out with the aim of finding out the implementation of the